Cognitive function impairment in multiple sclerosis patients: Medical education [Multipl sklerozlu olgularda kognitif fonksiyon bozukluklari] - (:unkn) unknown (Turkiye Klinikleri, 2006)
Cognitive impairment in multiple sclerosis occurs in an estimated 40-60% of cases. Learning and memory, attention, information processing, visuospatial abilities and executive functions 7re the most affected cognitive domains in multiple sclerosis. It is difficult to detect cognitive impairment during routine neurological examinations. Although the type of multiple sclerosis, and the duration of disease are correlated with cognitive impairment, decline in cognitive function, even in the early stages of the disease when there is no physical disability is reported. Lesion loads and cortical atrophy are also associated with cognitive impairment in multiple sclerosis patients. Although there is no special treatment for cognitive impairment in multiple sclerosis, reports suggest that disease-modifying medications are promising. Copyright © 2006 by Türkiye Klinikleri.
Keywords: Attention; Learning; Memory; Multiple sclerosis